(untitled) (Linguostylistic Studies, 2017)
The article presents a study of the conflict-type interaction in the political discourse. The emphasis is laid on the linguistic and pragmatic aspects of the phenomenon. The author highlights and generalizes the scholars’ views on the nature and types of conflicts aimed at discrimination between destructive and constructive conflicts. The article reveals the notion of communicative conflict as an interaction between communicants having counter-directed communicative tasks and deliberately violating the maxims of communication and explores the issues of conflict communication in the Ukrainian political discourse. It is proved that in the political communication the conflict has certain specificity associated with agonists: in the struggle for power rivals discredit and offend each other, aiming at the appropriate perlocutive effect. Communicative conflicts in the Ukrainian political discourse are characterized as conscious and unconscious dependencies on the realization of the communicative intent of the speakers. The basic role of verbal aggression in a communicative conflict is substantiated. The author argues that it defines both oppositional, single-vector speech behavior of communicators, and the use of emotionally-colored, predominantly negative evaluative vocabulary and appropriate communication strategies. The author analyzes the manifestations of conflict communicative interaction on the case study of politicians’ spontaneous communication during television talk shows («Shuster Live», «Freedom of Speech» and «Prime Time»), placing importance on the role of verbal and non-verbal means in the representation of the communicative conflict. The obtained results reveal the peculiar features of communicative behavior of the Ukrainian politicians in political interaction.